American sea power in the contemporary security environment. Issue 5 (20th October 2018) - Abenheim, Donald; Gingeras, Ryan; Russell, James A.; Wirtz, James J.; Young, Thomas-Durell; Twomey, Christopher
Abstract: This article assesses the relevance of US seapower in the contemporary security environment. This paper builds upon a rich literature on sea power, strategy, and maritime operations to assess recent factors and emerging geostrategic dynamics that are likely to affect American maritime strategy, while keeping sight of the principles that will endure regardless of shifting domestic and international politics. It places the application of sea power in an historic and strategic context to inform the policy choices that confront the administration in wielding elements of national power to further U.S. interests around the world. These issues come to the fore as the Trump Administration is seeking to expand the size of the Navy, with various proposals to increase the number of ships in the fleet to 350 vessels. The article presents these issues to highlight the building blocks available and the challenges faced by the United States as it seeks to reinvigorate its maritime strategy in the 21 st century.